Nutrient Sensing and Response Drive Developmental Progression in Caenorhabditis elegans. (31st January 2020) - Rashid, Sabih; Pho, Kim B.; Mesbahi, Hiva; MacNeil, Lesley T.
Abstract: In response to nutrient limitation, many animals, including Caenorhabditis elegans, slow or arrest their development. This process requires mechanisms that sense essential nutrients and induce appropriate responses. When faced with nutrient limitation, C. elegans can induce both short and long‐term survival strategies, including larval arrest, decreased developmental rate, and dauer formation. To select the most advantageous strategy, information from many different sensors must be integrated into signaling pathways, including target of rapamycin (TOR) and insulin, that regulate developmental progression. Here, how nutrient information is sensed and integrated into developmental decisions that determine developmental rate and progression in C. elegans is reviewed. Abstract : In response to nutrient deficiency, C. elegans can alter its developmental progression—promoting arrest or slowing development when nutrients are insufficient. Molecular mechanisms measure nutrient levels and communicate this information to conserved signaling pathways that promote or restrain development.